A giant aneurysm of sinus of Valsalva presenting with frequent syncopal attacks. (November 2022) - Zanganehfar, Mohammad Esmaeil; Shahandashti, Farshad Jalili; Shriati, Akram; Tayebi, Aida; Saedi, Sedigheh
Sinus of Valsalva aneurysm is a rare congenital or acquired aortic root anomaly. The aneurysm has the potential to compress the adjacent structures or rupture to other cardiac chambers with fatal consequences. Patients might be asymptomatic or present with nonspecific cardiac symptoms. Once the diagnosis is made, prompt surgical repair is generally required. Here, we present a young woman with frequent syncope who was found to have a giant sinus of Valsalva aneurysm as the underlying etiology.